Misdemeanorland: criminal courts and social control in an age of broken windows policing - Kohler-Hausmann, Issa (Princeton University Press, 2018)
"Felony conviction and mass incarceration attract considerable media attention these days, yet the most common criminal-justice encounters are for misdemeanors, not felonies, and the most common outcome is not prison. In the early 1990s, New York City launched an initiative under the banner of Broken Windows policing to dramatically expand enforcement against low-level offenses. Misdemeanorland is the first book to document the fates of the hundreds of thousands of people hauled into lower criminal courts as part of this policing experiment. Drawing on three years of fieldwork inside and outside of the courtroom, in-depth interviews, and analysis of trends in arrests and dispositions of misdemeanors going back three decades, Issa Kohler-Hausmann argues that lower courts have largely abandoned the adjudicative model of criminal law administration in which questions of factual guilt and legal punishment drive case outcomes. Due to the sheer volume of arrests, lower courts have adopted a managerial model--and the implications are troubling. Kohler-Hausmann shows how significant volumes of people are marked, tested, and subjected to surveillance and control even though about half the cases result in some form of legal dismissal. She describes in harrowing detail how the reach of America's penal state extends well beyond the shocking numbers of people incarcerated in prisons or stigmatized by a felony conviction. Revealing and innovative, Misdemeanorland shows how the lower reaches of our criminal justice system operate as a form of social control and surveillance, often without adjudicating cases or imposing formal punishment" -- jacket